2012
DOI: 10.3329/bjpt.v19i2.13133
|View full text |Cite
|
Sign up to set email alerts
|

Updated nomenclature and taxonomic status of the plants of Bangladesh included in Hook. f., the Flora of British India: Volume-II

Abstract: Sir Joseph Dalton Hooker in his second volume of the Flora of British India included a total of 2328 species in 416 genera under 28 natural orders (= families) of which 201 species in 104 genera under 20 natural orders are determined to have been recorded from the area now in Bangladesh. These taxa are listed with their updated nomenclature and taxonomic status as per ICBN following Cronquist’s system of plant classification. The current nomenclatural treatment revealed a total of 200 species in 109 genera und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The collected specimens have been critically studied and examined at the Department of Botany, University of Dhaka. Identifications were confirmed by matching the identified specimens housed at Dhaka University Salar Khan Herbarium (DUSH), and by consulting standard floras and recent literatures (9)(10)(11)(12)(13)(14)(15)(16) . Voucher specimens have been deposited in DUSH.…”
Section: Methodsmentioning
confidence: 99%
“…The collected specimens have been critically studied and examined at the Department of Botany, University of Dhaka. Identifications were confirmed by matching the identified specimens housed at Dhaka University Salar Khan Herbarium (DUSH), and by consulting standard floras and recent literatures (9)(10)(11)(12)(13)(14)(15)(16) . Voucher specimens have been deposited in DUSH.…”
Section: Methodsmentioning
confidence: 99%
“…Sonneratia apetala is an ecologically important tree species in mangroves of the Indo-Malayan region (Tomlinson, 1986). It is a light-demanding evergreen tree species belonging to the family of Sonneratiaceae (former Lythraceae) (Rashid and Rahman, 2012). In the Sundarbans, it mostly occurs in monospecific stands and often in association with Avicennia officinalis as a pioneer species in succession, preferably in moderate to high salinity zones (Iftekhar and Saenger, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For natural history, karyology, bioactive phytochemicals, ecophysiology, molecular biology and horticultural study of the genus Kalanchoe are suitable among crassulents (Osmond, 1978). Although Hooker (1886) documented eight genera including 40 species from the Indian subcontinent of which two species were explored from Bangladesh territory from the family Crassulaceae (Rahman and Rashid, 2012). Ahmed et al, (2008) reported five species named K. blossfeldiana, K. daigremonitnum, K. heterophylla, K. laciniata and K. pinnata from Bangladesh already.…”
Section: Introductionmentioning
confidence: 99%